Synthesis and Crystal Structure of Dimorphic Dibenzo[cde, opq]rubicene. Issue 60 (24th September 2019) - Suresh, Joghee R.; Whitener, Glenn; Theumer, Gabriele; Bröcher, Dirk J.; Bauer, Ingmar; Massa, Werner; Knölker, Hans‐Joachim
Abstract: Dibenzo[ cde, opq ]rubicene has been synthesized by an eight‐step reaction sequence including an iron‐mediated [2+2+1] cycloaddition and a flash vacuum pyrolysis as key steps. Two crystal modifications of the S‐shaped, planar polycyclic aromatic hydrocarbon have been obtained and characterized by X‐ray diffractometry. Abstract : An uncurved C30 fragment of C70 fullerene : Dibenzo[ cde, opq ]rubicene as a fragment of C70 fullerene was synthesized using an iron‐mediated [2+2+1] cycloaddition and flash vacuum pyrolysis. Two structural modifications were obtained showing perfectly planar single molecules in different packing modes.